Simulation of variation of flow in different types of pipe fittings using computational approach / Muhamad Azim Najmi Nor Azhari - Nor Azhari, Muhamad Azim Najmi (2022)
Pipe fittings such as valve, bend, tee, elbow, contraction and expansion are integral part any piping system found in chemical and allied industrial processes. However, Two types of energy loss predominate in fluid flow through a pipe network; major losses, and minor losses. Major losses are associated with frictional energy loss that is caused by the viscous effects of the medium and roughness of the pipe wall. The objective of this experiment is to analyze the variation of flow in different types of pipe fittings using computational approach. This experiment contains selection of pipe fittings, Modeling of selected pipe fittings in SolidWorks and ANSYS Software, after completing the Modeling the Analysis is carried out in ANSYS. The expectation of this experiment is should be increase as well as the value of head loss. Hence, the head loss should directly proportional to the square of the flow rate. In conclusion, multiple trials and errors simulating are required and possibly going to occur to obtain the perfect result on this experiment.